(untitled) (Research, Society and Development, 2020)
It is remarkable the importance that agribusiness has in the Brazilian economy, with almost 21.5% of GDP share is one of the most prominent sectors of the economic matrix. The focal company used for the present study reflects the importance of the sector, as it serves this sector with specific solutions through on-site service. In order to verify the performance of its sellers, key performance indicators (KPI) were built that used as a basis the expense of vehicle maintenance and the respective sales revenue. It was through the use of Excel software, the construction of comparative tables between the sellers’ performances, which in turn presented results regarding the indicators that indicate the Seller 1 130% more efficient than the seller 2, regarding the saving of resources for the maintenance. as well as annual revenues of the period. The study concludes not only with performance indication, but with relevant theoretical and practical guidelines for companies looking to implement performance indicators to optimize their results.